Controlling coal rock massif hydro-treating process by instrumental and geophysical methods - Klishin Vladimir (EDP Sciences, 2021)
Coal rock massif hydro-treating methods accompanied by crack initiation and propagation under influence of injected fluid pressure and applied for preventing gas-dynamic phenomena are studied in the article. The perspectives of applying acoustic methods for controlling the process of crack formation and effective preventive measures are also studied.